The Odd One Out? Revisiting the Belgian Welfare State - Cor Wagenaar (Footprint)
Michael Ryckewaert publication Building the Economic Backbone of the Belgian Welfare State. Infrastructure, planning and architecture 1945-1973 describes the evolution of the welfare state and Belgium, more specifically its spatial characteristics. This by now historical socio-political model had decidedly collectivist traits, culminating in the provision of social security networks and a vast expansion of the public domain. If collectivism was one of the key elements of the welfare state, the absence of centralized planning appears to make the Belgian variant somewhat problematic.